Laryngeal chondrosarcoma treated with conventional radiotherapy – case report and review of the literature - Roch-Zniszczoł, Agata; Księżniak-Baran, Dorota; Chmielik, Ewa; Goleń, Maria; Amrogowicz, Natalia; Gabryś, Dorota (Polish Journal of Pathology, 2022)
We report a case of a 68-year-old patient with laryngeal chondrosarcoma, whose first symptoms were hoarseness and gradually increasing dyspnoea, but there was no sign of disease in clinical examination, which postponed the diagnosis. The patient underwent complete laryngectomy and adjuvant conformal radiotherapy with a total dose of 70 Gy. The pathological assessment confirmed advanced laryngeal chondrosarcoma originating from thyroid cartilage. Imaging studies and directoscopy were performed, and they did not reveal recurrence or metastases of the disease for 6 years. Distant metastatic spread in the liver and lungs was confirmed 7 years after diagnosis, which caused hepatic insufficiency and led to death.